1969
DOI: 10.1079/bjn19690077
|View full text |Cite
|
Sign up to set email alerts
|

The quantitative significance of long-term regulation of food intake in the cow

Abstract: I. Six adult, non-pregnant, non-lactating, Friesian cows were used when fat and when thin to measure differences in the voluntary intakes of straw, hay and hay plus concentrates caused by the fatness of the animals. Measurements of digestibility, time of retention of food in the digestive tract, rate of breakdown of cotton threads in the ventral sac of the rumen and amounts of digesta in the reticule-rumen were included.2. The mean voluntary intakes of straw were similar for fat and thin cows. In absolute term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 14 publications
(4 reference statements)
6
32
0
Order By: Relevance
“…This agrees with the finding of Wright et al (1986) who reported that animals undergoing compensatory growth, following a lower feeding level the previous winter, had higher herbage intakes during the grazing season, both in absolute values and per kg live weight. The authors attributed this to a negative association between body fatness and voluntary food intake as earlier demonstrated for dairy (Bines et al, 1969) and beef (Hodgson et al, 1980) cows.…”
Section: Winter Feeding Levelmentioning
confidence: 70%
“…This agrees with the finding of Wright et al (1986) who reported that animals undergoing compensatory growth, following a lower feeding level the previous winter, had higher herbage intakes during the grazing season, both in absolute values and per kg live weight. The authors attributed this to a negative association between body fatness and voluntary food intake as earlier demonstrated for dairy (Bines et al, 1969) and beef (Hodgson et al, 1980) cows.…”
Section: Winter Feeding Levelmentioning
confidence: 70%
“…mesenteric and omental fat) apparently reduces the effective capacity of the cavity and this is associated with a reduced roughage intake by these animals (Tayler, 1959;Forbes, 1969;Bines, Suzuki & Balch, 1969). This reduction in intake is not necessarily an effect of a physical regulatory mechanism, since concentrate intake is also reduced in fat animals without the rumen being filled to capacity (Bines et al 1969). However, since fat cows do not eat enough hay even to maintain their weight, whereas thin cows eat enough of the same hay to gain weight (Bines, unpublished), the existence of a physical regulator appears likely.…”
Section: I7mentioning
confidence: 99%
“…When a ruminant is given a concentrated diet, the amount of material in the rumen at the end of a meal is less than when the diet consists mainly of roughage (Bines tx Davey, 1970;; thus, some factor has assumed greater importance than rumen fill in the regulation of food intake. At a single meal, there is considerable variation between different diets in the amount eaten, considerably less of an all-concentrate diet being eaten than of one containing a small proportion of roughage (Bines & Davey, 1970). However, when the total amount of food consumed in a day or longer period is considered, there is strong evidence that, with a concentrate diet, an animal's total intake of digestible energy is constant regardless of the exact composition of the ration fed (Dinius & Baumgardt, 1970).…”
Section: Metabolic Controlmentioning
confidence: 99%
“…There are also examples of so-called compensatory intake by sheep when their nutrient intake has previously been restricted (J. Eadie, unpublished data; Foot and Greenhalgh, 1969), which may be linked with the small amount of fat in the body of the undernourished animal. Bines, Suzuki and Balch (1969) found that the same six cows ate 30% more hay and 23 % more hay plus concentrates when they were thin than when fat.…”
mentioning
confidence: 93%
“…Hervey, 1969). Bines et al (1969) suggested that thin cows may have a greater rate of utilization of lipogenic substrates than fat cows and that the faster removal of the products of digestion might have stimulated higher intake.…”
mentioning
confidence: 97%